IMPLEMENTASI SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN - Nawawi, (UNISAN JURNAL, 2024)
This research explores the effectiveness of academic supervision techniques as a strategy to improve the quality of learning at SMP IT Bina Bangsa Sejahtera Kota Bogor. The approach used in this research is qualitative, using observation, interviews and document study as data collection methods. Sampling was carried out through purposive sampling and snowball sampling. The main focus of this research is academic supervision techniques, the implementation process, implementation, as well as the monitoring and evaluation process. Apart from that, the research also highlights the impact and follow-up carried out by the school principal on the results of academic supervision in improving the quality of learning in the school. Through the results of this research, it is hoped that a comprehensive picture can be found regarding the use of academic supervision in improving the quality of learning. Thus, this research has the potential to provide valuable insights for educational practitioners and other stakeholders in efforts to improve the quality of learning in the school environment.